2022
DOI: 10.1093/mrcr/rxac049
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with tofacitinib for relapse of rapidly progressive interstitial lung disease in anti-melanoma differentiation-associated gene 5 antibody-positive clinically amyopathic dermatomyositis

Abstract: Anti-melanoma differentiation-associated gene 5 (MDA5) antibody is associated with clinically amyopathic dermatomyositis (CADM) with rapidly progressive interstitial lung disease (RP-ILD). Recently, several studies have reported that tofacitinib, a Janus kinase inhibitor, might be effective for cases of new or refractory RP-ILD in anti-MDA5 antibody-positive CADM; however it is unknown whether tofacitinib can also be effective for relapsed cases. We herein report a relapsed case of RP-ILD in anti-MDA5 antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…2. A total of 21 articles, including 79 cases, were identified [5,6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Although Shirai et al [8] reported 13 patients treated with tofacitinib, only 8 patients were included in our analysis because data of the other 5 patients were combined with those treated without tofacitinib.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2. A total of 21 articles, including 79 cases, were identified [5,6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Although Shirai et al [8] reported 13 patients treated with tofacitinib, only 8 patients were included in our analysis because data of the other 5 patients were combined with those treated without tofacitinib.…”
Section: Literature Reviewmentioning
confidence: 99%
“…RMD Open RMD Open RMD Open therapy has also been reported. [6][7][8][9] However, there are still refractory patients even if treated with those therapies.…”
Section: What This Study Addsmentioning
confidence: 99%
“…They reported that tofacitinib was effective in three of five refractory cases to the triple therapy (glucocorticoids, cyclosporine, and IV-CY). Along with some case/case series reports suggesting the efficacy of tofacitinib for refractory MDA5-DM [24 ▪▪ ,29 ▪▪ ,30–41]. The results of two single-arm, open-label studies in China were published.…”
Section: Janus Kinase Inhibitorsmentioning
confidence: 99%